Evaluation of adherence to the Mediterranean diet with sustainable nutrition knowledge and environmentally responsible food choices - Yassıbaş, Emine; Bölükbaşı, Hatice (Frontiers in Nutrition, 2023)
Background: Dietary patterns and their possible effects on health and the environment are becoming increasingly important. It is thought that nutritionally balanced diets can also be compatible with environmental targets and, therefore, the Mediterranean diet (MD), which is regarded as a sustainable diet model, comes to the fore. This study was carried out to evaluate adherence to the MD with sustainable nutrition knowledge and environmentally responsible food choices and to determine the factors affecting adherence. Methods: A questionnaire prepared by the researchers was sent to individuals online and 1732 adults living in Turkey participated in this cross-sectional study. Adherence to the MD was evaluated with the Mediterranean Diet Adherence Screener (MEDAS). In addition, questions were asked about nutritional knowledge and environmentally responsible food choices to evaluate the sustainable nutritional behaviors of individuals. Results: Half of the participants (51.1% of men / 53% of women) adhere to the MD at a moderate level. Even the individuals with the highest adherence to the MD had low compliance with the recommendations for fruit (43.4%) and fish (37.3%) consumption. A one-unit increase in age, sustainable nutrition knowledge score, and environmentally responsible food choices score increases the MD adherence score by 0.08, 0.125, and 0.148 points, respectively (p<0.005). Individuals with high adherence to the MD avoid consuming genetically modified organism food more (p<0.001), prefer to consume environmentally labeled foods (p<0.001), and buy food more from local businesses (p<0.001), while they prefer to buy imported food less (p=0.034). Conclusion: The results of this study showed that some strategies should be developed to increase the adaptation of individuals to the MD and sustainable nutritional behaviors. Nutritionally adequate, sustainable, and eco-friendly nutritional behaviors should be encouraged to increase the possible health benefits of nutrition and minimize environmental effects. To promote sustainable nutrition, firstly it is important to determine the knowledge level of individuals concerning sustainable nutrition and, for this purpose, it is thought that an international valid sustainable nutrition knowledge assessment tool is needed.